The Originality of the Genre Characteristics of Uzbek Folk Legends - Makhmujonovna, Akhmedova Madinabonu (Journal of Sustainability in Integrated Policy and Practice, 2023)
This article discusses issues such as genre features, unique nature, system of images, and composition of Uzbek folk legends. Also, world and Uzbek scientists have summarized the theoretical views on the genre of myth.